Comparative nutritional compositions and proteomics analysis of transgenic Xa21 rice seeds compared to conventional rice. (15th July 2016) - Gayen, Dipak; Paul, Soumitra; Sarkar, Sailendra Nath; Datta, Swapan K.; Datta, Karabi
Highlights: Comparative nutritional composition and proteomics analysis of transgenic Xa21 rice seeds. Transgenic rice seeds were substantially equivalent to non-transgenic rice. No toxin or allergen was found due to expression of Xa21 gene. Abstract: Transgenic rice expressing the Xa21 gene have enhanced resistant to most devastating bacterial blight diseases caused by Xanthomonas oryzae pv. oryzae ( Xoo ). However, identification of unintended modifications, owing to the genetic modification, is an important aspect of transgenic crop safety assessment. In this study, the nutritional compositions of seeds from transgenic rice plants expressing the Xa21 gene were compared against non-transgenic rice seeds. In addition, to detect any changes in protein translation levels as a result of Xa21 gene expression, rice seed proteome analyses were also performed by two-dimensional gel electrophoresis. No significant differences were found in the nutritional compositions (proximate components, amino acids, minerals, vitamins and anti-nutrients) of the transgenic and non-transgenic rice seeds. Although gel electrophoresis identified 11 proteins that were differentially expressed between the transgenic and non-transgenic seed, only one of these (with a 20-fold up-regulation in the transgenic seed) shows nutrient reservoir activity. No new toxins or allergens were detected in the transgenic seeds.